Momen untuk patuh: Kepatuhan pajak melalui formulir prefilled dalam eksperimen laboratorium - Rizal Ash Shiddieqi; Eko Yudhi Prastowo; Yayan Puji Riyanto (Directorate General of Taxes, 2024)
Other than incurring financial burdens, paying taxes may also give rise to psychological liabilities to the taxpayers. They face uncertainty, anxiety, and confusion in the process that delimit their knowledge, intention, and ability to pay a fair amount of their taxes. One intervention that can be used to reduce these limitations is to use a prefilled form where information sourced from third parties will be automatically available so that the taxpayers can confirm the accuracy of the data provided. Different outcomes may emerge from the estimation of data accuracy and data classification provided in the prefilled form. This study aims to investigate the application of a pre-filled form in a self-assessment tax regime. Through a laboratory experiment, this study attempts to determine the impact of prefilled forms on tax compliance decisions made by individuals who compute their income taxes using the turnover presumptive tax system.